Use of laboratory tests in the emergency department of a hospital in Mexico - Pita, Carolina Jaimes (2024)
Objective: To describe the use of laboratory tests by medical staff assigned to the emergency department of a hospital in Mexico. Materials and methods: A descriptive cross-sectional study was conducted from March to July 2022 with data from 351 users of an emergency department. A non-probability convenience sampling was used. The sample included medical records of individuals over 18 years of age, of both sexes, who had a laboratory report and received medical attention in the emergency department in the past seven days. Pregnant women, postpartum women and individuals in shock were excluded. The variables collected from the records included sex, age, diagnosis, admission shift, type of emergency, requested analytes, documentation of laboratory report in clinical notes, analysis of laboratory results, and initiation or modification of medical treatment based on the findings. Descriptive statistics were performed using frequencies and proportions for qualitative variables. Results: The most common reason for consultation was abdominal pain, found in 11.96 % of the reviewed medical records. The most frequently requested analytes were blood count (98 %), blood chemistry (97 %) and serum electrolytes (88 %). The laboratory results were not documented in the medical notes in 63.8 % of cases, not analyzed in 68.9 % and not used to guide medical treatment in 72.1 %. This resulted in an unjustified expenditure of 57,529.34 Mexican pesos on laboratory tests. Conclusions: In seven out of 10 medical records, the laboratory tests did not contribute to initiating or modifying medical treatments. Strategies are needed to promote the appropriate use of analytes, including measures such as supervision, training and feedback, among emergency department medical staff.